1987
DOI: 10.1254/jjp.45.405
|View full text |Cite
|
Sign up to set email alerts
|

Surface epithelial cell damage induced by restraint and water-immersion stress in rats. Effects of 16,16-dimethyl prostaglandin E2 on stress-induced gastric lesions.

Abstract: Abstract-The time-course of gastric mucosal surface epithelial cell damage and macroscopically visible lesions in response to restraint and water-immersion stress (22°C) in rats was examined, and the effects on it of 16,16-dimethyl prostaglandin E 2 (dmPGE2) were compared with those of papaverine, timoprazole and atropine.The stress produced surface epithelial cell damage prior to visible lesion, the former increasing in severity with time and reaching a plateau 60 min later, by which time exfoliation of surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…For example, Mersereau and Hinchey (19) and Takeuchi et al (20) suggested that gastric hypermotility might be a major factor in the genesis of gastric lesions induced by indomethacin, by showing the close correlation between the lesion index and the motility index. Similar hypotheses have also been reported in other experimental ulcer models, including water-immersion stress-and various necrotizing agent-induced gastric lesions (13,21,22). Moreover, some antiulcer drugs such as beguhexate•CD and secretin were reported to possess inhibitory effects on gastric motility in normal rats or humans (23)(24)(25).…”
Section: Effects On Gastric Motilitysupporting
confidence: 74%
“…For example, Mersereau and Hinchey (19) and Takeuchi et al (20) suggested that gastric hypermotility might be a major factor in the genesis of gastric lesions induced by indomethacin, by showing the close correlation between the lesion index and the motility index. Similar hypotheses have also been reported in other experimental ulcer models, including water-immersion stress-and various necrotizing agent-induced gastric lesions (13,21,22). Moreover, some antiulcer drugs such as beguhexate•CD and secretin were reported to possess inhibitory effects on gastric motility in normal rats or humans (23)(24)(25).…”
Section: Effects On Gastric Motilitysupporting
confidence: 74%
“…Furthermore, electrical stimulation of vagus nerves (0.2 mA, 2 msec, 5 Hz, 10 min) produced gastric surface epithelial cell damage (15), and, in the present study, afforded similar protection against acidified ethanol as observed after stress. The surface epithelial cell damages induced by stress and vagal nerve stimulation resulted from gastric hypercontractions, be cause pretreatments with drugs that inhibited the gastric hypercontraction induced by stress and vagal nerve stimulation protected the cells against each type of damage (9,15). These results taken together indicate that the surface epithelial cell damage due to vagal overac tivity and consequent gastric hypercontrac tions may be an obligatory process for the appearance of mucosal protection by restraint and water-immersion stress.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, 1 -hr stress-loading, vagal nerve stimu lation and atropine significantly reduced the staining of gastric mucosa with dye. Since atropine inhibits stomach contractions (9), it would reasonable that this agent strongly reduces the mucosal folds and shows the protective effect against ethanol injury. How ever, in the present study, both stress and vagal nerve stimulation markedly increased stomach contractions, yet significantly re duced the mucosal folding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…saboten against stress-induced gastric lesions, since it is a widely used experimental model to induce acute stress ulcers in rats and is known for its reliable reproducibility. 19 A large number of natural products have been evaluated for their antiulcler effects while searching for possible candidates for new drugs or functional foods. 20 Opuntia species are also well known for its gastroprotective activities as demonstrated in various experimental models.…”
Section: Discussionmentioning
confidence: 99%